Motor laterality as a training skill. Learning effects over the change of lateral tendency - A. Bilbao; A. Oña (Asociación Española de Ciencias del Deporte, 2010)
The motor laterality is a traditional problem in the field of physical education. The explanation about this problem has been suported on genetics and byologics models, which considere it as a general human being condition to use one side of our body prior to the other one. This human disposition is determined by a brain hemisphere dominance that is behind all kind of behaviors; this hemisphere dominance, right or left, will be determined by the genetic code of each human subject, therefore the behaviors of choice between left and right for each limb of our body will be very difficult to modificate by learning. The present research is aim to explain motor laterality from a different model (behavioral model) to the biologic and genetic traditional model, where learnig be the key factor to understand it. By means a within-subject experimental design with three and four years old children we tried to probe the effects of learning in different lateralized behavior. We applied a technique of behavior modification which included, positive reiforcement, and feedback. We found that it is possible to change by learning the normal tendency to use one side of our body, left or right, instead the other side and to change, too, the knowledge of the side used. KEY WORDS: Laterality, handedness, dominane, motor control